Expression of inflammatory lipopolysaccharide binding protein (LBP) predicts the progression of conventional renal cell carcinoma - a short report - Kovacs, Gyula (Cellular oncology, 2017)
BackgroundThe mortality of conventional renal cell carcinoma (RCC) correlates directly with the presence or postoperative development of metastases. The aim of this study was to identify new markers associated with the postoperative progression of conventional RCC.MethodsTissue microarrays (TMA) of conventional RCC from a cohort of 414 patients were analysed by immunohistochemistry for expression of the lipopolysaccharide binding protein (LBP), which was identified as a candidate biomarker through Affymetrix U133 Plus 2.0 array analysis. Univariate and multivariate Cox regression models were addressed to cancer-specific survival in association with age, sex, clinicopathological parameters and LBP expression. The survival time of the patients was estimated by Kaplan-Meier analyses, and comparisons of survival curves were made using the Log rank test.ResultsUnivariate analysis revealed an association of patient survival with all clinicopathological parameters tested and LBP expression. In multivariate analysis only T classification, grade and LBP staining showed a significant association with postoperative cancer-specific survival (p < 0.001). LBP expression was found to be associated with a poor patient survival in Kaplan-Meier analyses. The estimated median survival time for patients with tumours showing LBP expression was 74 months, whereas the overall survival time was 142 months.ConclusionLBP expression in conventional RCC defines a group of patients at a high risk of postoperative progression and may help to direct optimized active surveillance and timely adjuvant therapy.
Gesehen am 31.10.2018